Between Aspiration and Reality: Educational and Professional Trajectories of Young Women - Huber, Evéline; Bergman, Manfred Max (Swiss Journal of Educational Research, 2018)
This article aims at examining the influence of significant others on young women professional aspiration and actual profession. Young women born between 1983 and 1989 were interviewed about their dream job and their actual occupation in the present. Qualitative content analysis allowed to identify four groups of significant others who exerted different influences on the young women. Results show that the strongest gendering can be found in families, particularly via the mother’s influence. While mothers are perceived as emotionally supportive, fathers tend to appear as a contact person for the funding of further education. Typically, female professions such as kindergarten teacher often appear as a dream job in early childhood, which continue the strongly gendered nature of women’s educational and occupational pathways.